PENGARUH IKLIM ORGANISASI SEKOLAH TERHADAP MOTIVASI KERJA GURU DI SEKOLAH DASAR - Ageng Satria Pamungkas; Jatun Jatun; Sariah Sariah (Jurnal Ilmiah Ibtida: Jurnal Prodi PGMI STIT Pemalang, 2022)
This study aims to determine (1) Quality of school organizational climate, (2) Quality of teacher’s work motivation, (3) Is there influence of school organizational climate on teacher work motivation dan (4) The magnitude of the school organizational climate on teacher work motivation in public elementary schools 1 & 3 Bojanegara. This study use descriptives quantitative research methods. This research was carried out in two cycles and each cycle consisted of four stages, namely planning, implementation, observation, and reflection. The work motivation of teachers at SD N 1 and 3 Bojanegara obtained data from 13 respondents who were observed, so that there were 7 respondents or 58,8% in the high category, 3 respondents or 23%, in the medium category and 3 respondents in the low category. So that the work motivation of teachers at SD N 1 Bojanegara can be categorized as a quite good. There is a significant influence between school organizational climate on teacher work motivation, which is obtained with a significance of 0,006, while the influence of sschool organizational climate variables increases by 1% it will be able to effect the teacher’s work motivation variable